STUDY ON MANUFACTURING OF REBON SHRIMP PROTEIN HYDROLYSATE (Acetes erythraeus) USING BACTERIA Lactobacillus plantarum WITH DIFFERENT CONCENTRATIONS - Ibrahim Teguh Prawira; Suparmi Suparmi; Ira Sari (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2021)
ABSTRACT Rebon srimp (Acetes erythraeus) is one of the aquatic commodities that has huge potential, due to its abundance in Rohil Regency which has not been utilized optimally. This study examines the potential of protease enzymes from lactic acid bacteria (Lactobacillus.plantarum) as an alternative in the hydrolysis process. The purpose of this study was to determine the best concentration of bacteria L. plantarum in the manufacture of rebon shrimp protein hydrolysate and to determine the quality of the produced rebon shrimp hydrolysate. The method used in this research is experimental, namely by refining, fermentation and hydrolysis with different concentrations consisting of 3 treatment levels, namely P1 (15%), P2 (20%), and P3(25%). The results of the research obtained the best treatment is P3 treatment with the use of bacteria concentration L. plantarum of 25% produces the chemical composition of the hydrolysate rebon covering of moisture content 81.41% ww, ash content of 1.15% dw, fat content 6.98% dw, protein content is 82.17% dw, and the resulting pH value is 5.1. The results of the analysis of the types and levels of amino acids in treatment P3 (L. plantarum 25%) produced 9 types of essential amino acids with the highest amount, namely leucine (1.298%) and 8 non-essential amino acids, namely glutamic acid (2.058%), then the enzyme treatment protease frombacteria L. plantarum can be an alternative in the hydrolysis process. Keywords:Aceteserythraeus; L. plantarum; chemical composition; amino acids